2010
DOI: 10.1099/mic.0.032342-0
|View full text |Cite
|
Sign up to set email alerts
|

PssA is required for α-amylase secretion in Antarctic Pseudoalteromonas haloplanktis

Abstract: Extracellular protein secretion is an essential feature in bacterial physiology. The ability to efficiently secrete diverse hydrolytic enzymes represents a key nutritional strategy for all bacteria, including micro-organisms living in extreme and hostile habitats, such as cold environments. However, little is known about protein secretion mechanisms in psychrophilic bacteria. In this study, the recombinant secretion of a cold-adapted α-amylase in the Antarctic Gram-negative Pseudoalteromonas haloplanktis TAC12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The results of the RT-PCR experiments (Figure S3 ) showed that a PSHAb0219 gene transcription was clearly detected in the RNA samples extracted from P. haloplanktis TAC125 cells grown in both conditions. Several experiments were then attempted to delete the PSHAb0219 gene by using genetic tools for the creation of insertion/deletion mutants already available (Parrilli et al, 2010 ). However, these experiments were not successful probably due to the fact that PSHAb0219, in tested conditions, is likely to be an essential gene.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the RT-PCR experiments (Figure S3 ) showed that a PSHAb0219 gene transcription was clearly detected in the RNA samples extracted from P. haloplanktis TAC125 cells grown in both conditions. Several experiments were then attempted to delete the PSHAb0219 gene by using genetic tools for the creation of insertion/deletion mutants already available (Parrilli et al, 2010 ). However, these experiments were not successful probably due to the fact that PSHAb0219, in tested conditions, is likely to be an essential gene.…”
Section: Resultsmentioning
confidence: 99%
“…, 2004). Attempts to inactivate this gene in P. haloplanktis TAC125 were carried out using recently developed methods involving a suicide vector derived from a psychrophilic cryptic plasmid and successfully used to knockout non‐essential genes (Parrilli et al. , 2008; 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the mesophilic bacterium, the trigger factor gene is not essential for growth at any temperature (Deuerling et al, 1999;Kramer et al, 2004). Attempts to inactivate this gene in P. haloplanktis TAC125 were carried out using recently developed methods involving a suicide vector derived from a psychrophilic cryptic plasmid and successfully used to knockout non-essential genes (Parrilli et al, 2008;2010). It was, however, not possible to obtain TF deletion mutants of the Antarctic bacterium after recovery at either 4°C or 18°C.…”
Section: The Trigger Factor Is the Major Cold Acclimation Protein Andmentioning
confidence: 99%